Star names : their lore and meaning - Allen, Richard Hinckley, 1838-1908.; Allen, Richard Hinckley, 1838-1908. (New York : Dover Publications, 1963)
Ancient observations and folklore provide the basis for an exploration of astronomical nomenclature.
Solar zodiac -- Lunar zodiac -- Constellations -- Galaxy.
"Formerly titled: Star-names and their meanings."
"An unabridged and corrected republication of the work first published by G.E. Stechert in 1899"--Title page verso.
Includes bibliographical references and indexes.
"T 1079."
Keywords: Constellations; Constellations